Factors influencing the retention of academic staff at IPTS: A study at IPTS Bandar Baru Bangi and Kajang / Syahira Md Yusop - Md Yusop, Syahira (Faculty of Business and Management, 2006)
Academic staff means a person appointed on a permanent basis to serve the institution in the capacity of providing professional teaching related to academic programmes with the highly qualified to increase the number of academic talent in education industry.The academic staff of a higher education institution is a key resource. However, retention of academic staff has become a primary concern in many IPTS for several reasons. The main purpose of this study is to identify the factors influencing the retention of academic staff at IPTS. Moreover, the researcher would like to determine the most important factor to retain the academic staff at IPTS and also to examine the relationship between retention factors and retention of academic staff. The data came from a study of 50 respondents who are academic staff at 5 selected IPTS at Bandar Baru Bangi and Kajang. The variables are institution culture and value, institution reputation and position, conditions of employment, personal and professional development, teaching climate, research climate and work environment. A probability sampling technique and simple random sampling has been chosen to use. Data is analyzed using SPSS software by frequency, Pearson correlation and hypotheses testing. From the findings all the factors has positive and negligible relationship with the retention. Finally the only two of the variable has significant relationship with the retention of academic staff which is conditions of employment and teaching climate.